Differences in Symptomatic Presentation and Cognitive Performance Among Participants With LATE-NC Compared to FTLD-TDP. Issue 11 (1st October 2021) - Teylan, Merilee A; Mock, Charles; Gauthreaux, Kathryn; Culhane, Jessica E; Jicha, Gregory; Chen, Yen-Chi; Chan, Kwun C G; Kukull, Walter A; Nelson, Peter T; Katsumata, Yuriko
Abstract: Transactive response DNA-binding protein 43 kDa (TDP-43) is aberrantly aggregated and phosphorylated in frontotemporal lobar degeneration of the TDP-43 type (FTLD-TDP), and in limbic-predominant age-related TDP-43 encephalopathy neuropathologic change (LATE-NC). We examined data from the National Alzheimer's Coordinating Center to compare clinical features of autopsy-confirmed LATE-NC and FTLD-TDP. A total of 265 LATE-NC and 92 FTLD-TDP participants were included. Cognitive and behavioral symptoms were compared, stratified by level of impairment based on global clinical dementia rating (CDR) score. LATE-NC participants were older at death, more likely to carry APOE ε4, more likely to have Alzheimer disease neuropathology, and had lower (i.e. less severe) final CDR global scores than those with FTLD-TDP. Participants with FTLD-TDP were more likely to present with primary progressive aphasia, or behavior problems such as apathy, disinhibition, and personality changes. Among participants with final CDR score of 2–3, those with LATE-NC were more likely to have visuospatial impairment, delusions, and/or visual hallucinations. These differences were robust after sensitivity analyses excluding older (≥80 years at death), LATE-NC stage 3, or severe Alzheimer cases. Overall, FTLD-TDP was more globally severe, and affected younger participants, whereas psychoses were more common in LATE-NC.